2011
DOI: 10.1103/physrevb.84.041108
|View full text |Cite
|
Sign up to set email alerts
|

Stripes in the two-dimensionalt-Jmodel with infinite projected entangled-pair states

Abstract: We simulate the t-J model in two dimensions by means of infinite projected entangled-pair states (iPEPS) generalized to arbitrary unit cells, finding results similar to those previously obtained by the density-matrix renormalization group (DMRG) for wide ladders. In particular, we show that states exhibiting stripes, i.e. a unidirectional modulation of hole-density and antiferromagnetic order with a π-phase shift between adjacent stripes, have a lower variational energy than uniform phases predicted by variati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
179
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 41 publications
9
179
6
Order By: Relevance
“…The main question in this context is whether the ground state is homogeneous with the possible signatures of d-wave pairing [9,10] or it possesses inhomogeneous state, e.g., phase separation [11] or stripe order [12]. So far, no agreement on this issue has been reached yet.…”
Section: Introductionmentioning
confidence: 88%
“…The main question in this context is whether the ground state is homogeneous with the possible signatures of d-wave pairing [9,10] or it possesses inhomogeneous state, e.g., phase separation [11] or stripe order [12]. So far, no agreement on this issue has been reached yet.…”
Section: Introductionmentioning
confidence: 88%
“…Nevertheless these results indicate that from the point of view of local energetics the PDW state is very competitive and would most likely be the ground state for some extension of the Hamiltonians that were studied. A very recent and numerically intensive calculation using infinite projected entangled pair states (an extension of the density matrix renormalization group) by Corboz et al 28 have found stripe states coexisting with superconductivity in the 2D t − J model but has not yet investigated the presence (or absence) of a PDW state.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the iPEPS can be systematically controlled by the so-called bond dimension D. Details on the method can be found in refs. [4,5].Figure 1(a) shows an example of a jump in n(µ) for V = 1.72 between the two densities n 1 ≈ 0.11 and n 2 ≈ 0.89 obtained with iPEPS. For densities in between these two values there is no stable homogenous solution, because it is energetically favorable for the system to split into two regions, one with density n 1 and the other one with n 2 .…”
mentioning
confidence: 99%
“…The accuracy of the iPEPS can be systematically controlled by the so-called bond dimension D. Details on the method can be found in refs. [4,5].…”
mentioning
confidence: 99%